Monitoring Critical Areas and Unauthorized Access Using RFID Technology - عكسة, كريمة; حراق, محي الدين (khazzartech الاقتصاد الصناعي, 2023)
Monitoring is the function of observing all human or environmental activities to supervise, control or even react to a particular case; this is called supervision or monitoring. Radioidentification technology, known by the abbreviation RFID (Radio Frequency Identification), is one of the technologies used to remotely retrieve, store, and even process data. It is topical technology and one of the technologies of industry 4.0 that fits into many areas of daily life, including surveillance and access control. The objective of this article is to show how to protect and monitor in real-time critical industrial areas and all types of unauthorized access by any person (employees, visitors…) using RFID technology, and this through examples of simulation using a simulator dedicated to sensor networks.